Initiating revolutions for optical manipulation: the origins and applications of rotational dynamics of trapped particles. Issue 1 (1st January 2021) - Bruce, Graham D.; Rodríguez-Sevilla, Paloma; Dholakia, Kishan
ABSTRACT: The fastest-spinning man-made object is a tiny dumbbell rotating at 5 GHz. The smallest wind-up motor is constructed from a DNA molecule. Picoliter volumes of fluids are remotely controlled and their viscosity precisely measured using microrheometers based on miniscule rotating particles. Theoretical predictions for extraordinarily weak forces related to the presence of dark matter, dark energy and vacuum-induced friction might be revealed, and the surprising properties of light have already been experimentally evidenced. All of these exciting landmarks have only been possible thanks to the torque exerted by light, which enables rotation of an optically trapped particle. Here, we review how light can impart torque on optically trapped particles, paying close attention to the design of the properties of both the particle and the light field. We detail how the maximum achievable rotation speed is limited by the environment, but can simultaneously be used to infer properties of the surrounding medium and of the light field itself. We also review the state-of-the-art applications of light-driven rotors, as well as proposals for the next generation of measurements, particularly at the classical-quantum interface, which can be performed using rotating optically trapped objects. Graphical abstract: uf0001